SISTEM PENGELOLAAN ADMINISTRASI PERSURATAN DAN PENGARSIPAN - Muhammad Soni Amrulloh (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The pupose of the research is to know and explain the correspondence management in man 3 kediri. A letter is an importantinstrument in a company because it involves activities, both from outside in within the school itself. This research is a qualitative research with a case study research methoddata collection was done by means of obsevation interviews, and documentation. Interviews were conducted to selected informants through purposive sampling tecnique with predetermined criteria. The object in this research the corresondence system whil the research subjects are the arcive and correspondence staff in man 3 kediri the resultts of this study indicate that the procedures for receiving and sending letters in man 3 kediri have met the standards which include sorting, recording, copying, directing, and delivering activities. Meanwhile, when viewed from the data storage, see man 3 kediri.